Kajian Literatur Tentang Penerapan Aplikasi Wordwall Terhadap Hasil Belajar pada Materi Mengubah Bentuk Energi di Kelas IV SD - Zn, Risma Ayu Oktavia; M, Hanny Nur Jan’nah; Setiyawan, Hery (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The problem of low motivation and learning outcomes among elementary school students remains a challenge in the education sector in Indonesia. One alternative solution is the utilization of interactive technology-based learning media, such as the Wordwall application. This study aims to examine the effectiveness of using Wordwall in improving student learning outcomes on the topic of